Knowledge-Intensive Business Services and Business Consulting Services in Romanian Changing Economic Environment - Iacob Cătoiu; Liviu Tudor; Cristian Bisa (Amfiteatru Economic Journal, 2016)
In today's economy companies are faced with the necessity of accelerated change. Stepping up the pace of change requires the use of advanced knowledge-intensive services and cooperation with change management professionals. Therefore, there should be a positive correlation between the dynamic of the overall economy and the development of the market for knowledge-intensive business services and, in particular, for management consulting services. This paper aims to explore this correlation in the Romanian current economic context, providing a description of the market for business consulting services, an analysis of the territorial distribution of knowledge-intensive business services in Romania and a multidimensional analysis of the statistical relation between knowledge-based services / management consultancy services and the economic performance indicators. The activity of knowledge-intensive services providers has a positive and strong impact on the national and regional economy, fact determined by the statistical analysis on public data available at National Trade Register Office during 2008-2014. The effects of business consulting projects are visible in clients' financial results after one or two years. Currently, Romanian enterprises are more likely to request consulting services in order to increase their profitability, instead of their income.
Keywords: M21; O47; D83; C32; H12; 330; Knowledge-intensive business services; business consulting; change management; Romanian economic environment